SIMPLE QUANTIFIED AND VALIDATED STABILITY INDICATING STRESS DEGRADATION STUDIES OF ORAL ANTI-DIABETIC AGENT DAPAGLIFLOZIN BY RP-HPLC METHOD - MURUGESAN, ARULSELVAN; MATHRUSRI ANNAPURNA, MUKTHINUTHALAPATI (International Journal of Applied Pharmaceutics, 2022)
Objective: This method is focused on developing a precisely simplified and more accurate Reverse Phase–High Pressure Liquid Chromatography (RP-HPLC) method for the determination of Dapagliflozin in bulk and pharmaceutical dosage form as per guidelines of International Council for Harmonization (ICH). Methods: Evaluation and validation carried out using the RP-HPLC ZORBAX (C18) column (250 x 4.6 mm, 5 μm particle size) with a mobile phase consisting of Phosphate Buffer: Acetonitrile: Methanol in a ratio of 55:40:05 (v/v/v) at a flow rate of 1 ml/min with an injection volume of 10 μl. Results: Dapagliflozin was eluted at 2.12±0.05 min and detected at 225 nm. The regression equation y = 55762 x-29679 found to be linear with correlation coefficient r2 value of 0.9997. The developed RP-HPLC method was conveniently validated as per the ICH guidelines and found method was robust, sensitive, accurate, selective, specific, precise and linear. Conclusion: The proposed method was found to be accurate, precise, and robust for API and pharmaceutical dosage form as per experimentation analysis. The above developed method was found to be satisfied for Active Pharmaceutical Ingredient (API) and pharmaceutical formulation of Dapagliflozin to study its degradation products.